Evaluation – The Cinderella Science of ICT in Health - Rigby, M. (Yearbook of Medical Informatics, 2006)
Information systems are expensive to create, and consume resources in their operation. They are justified in order to achieve clearly defined objectives in health service quality and efficiency. To ensure that these objectives are being met, and in order to build up an evidence-base to support well focused policies, systems, and practice, evaluation would seem to be fully justified and indeed essential. However, there are major factors jeopardising good evaluation practice, ranging from reluctance to commit resources or expose decisions to scrutiny, through to lack of appreciation of the full range of dimensions which should be studied. This paper seeks to create fuller appreciation of the issues and their importance.Experiential and literature reviews form the basis of an exposition of principles, methods, and key current activities.A summary has been produced of the key challenges to health ICT evaluation, and its adverse comparison with other sectors. An explanation of the viewpoints and levels of health information evaluation is followed by a short history of principal milestones, current scientific methodology activity, and key collaborative activities.The need for a stronger commitment to health ICT evaluation is demonstrated if the application of health informatics systems is to receive due recognition as scientifically and empirically justified. Commitment of resources and scientific endeavour are needed, and thus the recent Declaration of Innsbruck, arising out of an event sponsored by the European Science Foundation, is timely and fully justified.
Keywords: Evaluation; information systems